The Effect Of Investor Sentiment On Stock Returns: Insight From Emerging Asian Markets - V. Anusakumar, Shangkari; Ali, Ruhani; Hooy , Chee Wooi (Asian Academy of Management (AAM), 2017)
This paper investigates the link between investor sentiment and stock returns in emerging Asian markets. Two dimensions of sentiment are examined: stock specific sentiment and market wide sentiment. Using panel regression with firm fixed effects, we show that stock specific sentiment strongly and positively affects stock returns after controlling for firm characteristics. Overall, there is a positive relationship between market wide sentiment and returns but the relationship does not hold at the country level. For individual countries, we detect substantial country-to-country variations in the influence of market wide sentiment on returns. The evidence also suggests that stock specific sentiment may have a greater influence on returns than market specific sentiment. Furthermore, the effect of investor sentiment on stock returns in emerging Asian markets generally persists after accounting for macroeconomic factors.